1998
DOI: 10.1038/sj.onc.1201893
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic activation of a human cyclin A2 targeted to the endoplasmic reticulum upon Hepatitis B virus genome insertion

Abstract: Cyclins are major cell cycle regulators which role in malignant transformation remains controversial. In this report we describe a new mechanism of cyclin oncogenic activation. We demonstrate that an altered form of cyclin A2 (S2A) which N-terminal part is replaced by the hepatitis B virus envelope protein transforms normal rat kidney cells and cooperates with ras to transform rat embryo ®broblasts. In contrast, neither the viral moiety, nor a full length or N-terminally deleted cyclin A2 show these oncogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…It is not clear whether a cyclin A1/CDK complex may phosphorylate some inappropriate targets in the cytoplasm. However, it has been shown that cellular transformation resulted from the ectopic expression of cytoplasmic cyclin A2 was linked to the aberrant phosphorylation of cyclin A2/CDKs on some substrates (Berasain et al, 1998). Our results and previous reported studies suggest a new mechanism of cyclin-related cellular transformation, in which abnormal cytoplasmic localization instead of, or in addition to elevated levels of the proteins are involved in the transformation process.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It is not clear whether a cyclin A1/CDK complex may phosphorylate some inappropriate targets in the cytoplasm. However, it has been shown that cellular transformation resulted from the ectopic expression of cytoplasmic cyclin A2 was linked to the aberrant phosphorylation of cyclin A2/CDKs on some substrates (Berasain et al, 1998). Our results and previous reported studies suggest a new mechanism of cyclin-related cellular transformation, in which abnormal cytoplasmic localization instead of, or in addition to elevated levels of the proteins are involved in the transformation process.…”
Section: Discussionsupporting
confidence: 51%
“…It has also been reported that altered distribution of p27 is correlated to Barrett's associated adenocarcinoma (Singh et al, 1998). A mutant version of cyclin A2, induced by an insertion of human hepatitis B virus, was observed in hepatocellular carcinoma and shown to be predominantly cytoplasmic rather than nuclear (Wang et al, 1990;Berasain et al, 1998). A direct association between cytoplasmic cyclin A2 and oncogenic transformation was demonstrated in subsequent studies in which a non-viral signal was used to target cyclin A2 to the endoplasmic reticulum, which resulted in several features of cellular transformation (Faivre et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, Woodchuck Hepatitis Virus, the Hepadnavirus infecting woodchucks, induces liver cancer by recurrent targeting of myc oncogenes (c-myc, N-myc and N-myc2) (Buendia, 1992), and rare cases of HBV integration into key cellular genes have been reported in human liver tumors (retinoic acid receptor beta (Dejean et al, 1986) and Cyclin A (Wang et al, 1990)) and cell lines (mevalonate kinase (Graef et al, 1994)). Moreover, earlier studies have demonstrated that HBV-DNArelated RAR and Cyclin A insertional mutagenesis has transforming activity in vitro and in vivo (Garcia et al, 1993;Berasain et al, 1998). However, recurrent HBV integration sites targeting cellular genes have never been identified in the past (Matsubara and Tokino, 1990), suggesting that insertional mutagenesis does not play a significant role in liver carcinogenesis.…”
mentioning
confidence: 99%
“…In fact, the HBV genome has been found integrated into the Retinoic Acid Receptor Beta (Dejean et al, 1986) and the Cyclin A2 (Wang et al, 1990) gene in two isolated HCCs. Interestingly, further analyses have demonstrated that the mutation of these two genes identi®ed in the tumorous tissue has transforming and tumorigenic properties (Berasain et al, 1998;Garcia et al, 1993). Thus, studies on HBV-related insertional mutagenesis allowed to isolate two previously unknown human genes, which play a major role in cell di erentiation and proliferation, and to prove their role in carcinogenesis.…”
mentioning
confidence: 99%